Conversations of a group of Physics’ teachers about textbooks’ images: an exploratory study - María de los Ángeles Fanaro; María Rita Otero (Investigações em Ensino de Ciências, 2007)
In this work we realize an exploratory study based on a group of discussion with three Physics teachers to whom there were projected images of Physics books while questions were formulated. There is explored the conscience that they have on the complexities of the images, and the didactic analysis that they realize when they are placed in situation to think brings over of how they use them. Of the conversation there are inferred the meanings that emerge of your actions. This work continues a quantitative previous work, in which we study the conceptions of the teachers of diverse curricular areas, on the images in the educational materials (Fanaro, et. al., 2004). More than the half of the teachers integrates a set that we name "Image optimists”, treating itself about individuals that they support the " popular psychology "conceptions (Otero, 2002; Otero, Greca, Silveira, 2003). The results of the present work with a small group of discussion, suggest that these teachers lack theoretical tools that they make possible to realize a didactic analysis of the images. The problematics of the images in the education in sciences, would have to integrate the formation of the future teachers and the training of those who are in service. Finally, we propose some recommendations to think didactic actions relative to the visual language.